Now you see me, now you don't: dynamic flash coloration as an antipredator strategy in motion. (August 2018) - Murali, Gopal
Abstract : Animals employ a diverse array of colorations to avoid being consumed by predators. While much research has focused on patterns that work when the animal remains stationary, studies examining the role of colour patterns that function when it moves to avoid predation remain scarce. Here, I propose and test the hypothesis that striking colorations that change dynamically through time, for example bright colours on the dorsal wing surface in combination with cryptic/contrasting ventral coloration (or vice versa) as seen in many insects and birds, serve to protect the moving animal from predation. This idea is analogous to a well-known visual illusion termed the flash lag effect which occurs because of the constraints in estimating the instantaneous position of a moving object due to the inherent neural processing delay. I performed a virtual predation experiment using a touch screen where human participants were asked to capture a moving stimulus that changed colour dynamically through time or remained constant. I found stimuli with dynamic colour change were caught less often and less accurately than a colour-static white or background-matching stimulus but were equally difficult to capture as a colour-static average grey under certain conditions. These results suggest that dynamic colour change is effective in lowering the probability of capture, but this benefit is not unique, as the colour-static average grey stimulus had a similar advantage. Overall, the study thus presents the first clear evidence that animals that change colours during movement could gain significant protection against predation, probably by misrepresenting the prey's location. Highlights: Camouflage during motion might be ineffective against predation. I tested whether dynamic colour change could be advantageous during motion. Stimulus with dynamic coloration was caught less than a background matching stimulus. Dynamic coloration could help reduce predation when prey is moving.